Evaluation of Copper Hydroxide Bactericide for the Management of Common Bacterial Blight (Xanthomonas axonopodis pv. phaseoli) of Common Bean in Eastern Amhara, Ethiopia - Kassaw, Admasie; Tiruneh, Abiye; Abtie, Abate; Ayalew, Abebi; Desale, Tesfaye; Endris, Kedir (Department of Agronomy and Horticulture, IPB University, 2025)
Common bacterial blight constitutes a major constraint to common bean production in Ethiopia. To evaluate the efficacy of seed treatment and varying frequencies of foliar application of copper hydroxide for disease management, a field experiment was conducted at the Sirinka, Jari, and Cheffa research sites during the 2022 and 2023 growing seasons. The study employed a randomized complete block design with three replications. Eight treatments were assessed, including copper hydroxide seed treatment alone, seed treatment combined with one, two, or three foliar spray applications, and an untreated control. Data on disease severity, yield, and yield components were subjected to analysis of variance using GenStat version 18.0 software. The combined mean analysis revealed that the highest area under the disease progress curve (AUDPC) value (957) was recorded in the seed-treated plots receiving two foliar sprays, while the lowest AUDPC value (518.6) was observed in the untreated control plots. Seed yield ranged from 1408 kg.ha-1 in the control treatment to 2397 kg.ha-1 in plots treated with copper hydroxide seed treatment plus two foliar sprays. The highest marginal rate of return (2214.2%) was attained with seed treatment alone, whereas a single foliar spray application yielded a return of 102.92%. Based on these findings, it is recommended that copper hydroxide bactericide be applied as a seed treatment at a rate of 300 g.100 kg-1 of common bean seed at planting, supplemented with a single foliar spray at the onset of disease, as this approach provides the greatest net economic benefit compared to other treatments and the control.